Production of non-natural 5-methylorsellinate-derived meroterpenoids in Aspergillus oryzae - Tang, Jia; Zhang, Yixiang; Matsuda, Yudai (Beilstein Journal of Organic Chemistry, 2024)
Fungal meroterpenoids are diverse structurally intriguing molecules with various biological properties. One large group within this compound class is derived from the aromatic precursor 3,5-dimethylorsellinic acid (DMOA). In this study, we constructed engineered metabolic pathways in the fungus Aspergillus oryzae to expand the molecular diversity of meroterpenoids. We employed the 5-methylorsellinic acid (5-MOA) synthase FncE and three additional biosynthetic enzymes for the formation of (6R,10′R)-epoxyfarnesyl-5-MOA methyl ester, which served as a non-native substrate for four terpene cyclases from DMOA-derived meroterpenoid pathways. As a result, we successfully generated six unnatural 5-MOA-derived meroterpenoid species, demonstrating the effectiveness of our approach in the generation of structural analogues of meroterpenoids.
Keywords: biosynthesis; meroterpenoids; natural products; pathway engineering; terpene cyclases